Exploring Grammar Learning Strategies: A Descriptive Study of EFL University Students at Aceh Province - Syarfuni Syarfuni; Sarmadan Sarmadan; Verawati Verawati (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study examines grammar learning strategies used by the English Language Education Study Program students in Aceh Province. The main problem raised is the difficulties students face in applying the grammar learned to daily communication. This study aims to explore the strategies applied in grammar learning and the factors that affect the effectiveness of these strategies in Aceh. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation. Data was obtained from students and lecturers in the English Education Study Program at several universities in Aceh. The study results show that although various grammar learning strategies have been implemented, students still find connecting theory with language practice in daily life challenging. These findings reveal the importance of teaching grammar that is more contextual and focuses on real communication practices. This research contributes to the development of grammar learning theory and practice and provides recommendations for teaching that are more applicable and relevant to students' local needs. However, this study also has limitations, especially regarding sample coverage limited to one province, which can be used as an opportunity for further research by expanding the region's scope and data collection techniques.